Mobile Phone to Youngsters: Necessity or Addiction - Ahmed, Ishfaq; ., Khadija Aijaz Perji (Information Management and Business Review, 2011)
This study focuses on exploring the pattern of mobile phone usage among youngsters in Pakistan to delineate the extent of addictive behavior towards its usage. For this purpose questionnaires were used to elicit the responses. University students were selected as population and simple random sampling technique was used. Sample was consisting of 500 students out of which 400 students responded back comprising 80% response rate for this research. Findings of this study revealed that majority respondents are able to have definite priorities between their responsibilities & commitments and their cell phone usage. Very few are those who always exhibit the extreme addictive behaviors and rest is the majority who are not frequently involved in addictive usage patterns. Thus, youngsters use their cell phones under reasonable limits and do not tend towards extreme behaviors leading towards addictive cell phone usage.